Analisis Transparansi Dan Akuntabilitas Pengelolaan Dana Bantuan Operasional Sekolah (Studi Kasus Pada SD Negeri 3 310 Assorajang Kabupaten Wajo) - Nurul Hidayah; M. Ridwan Tikollah; Mukhammad Idrus (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2025)
This study aims: (1) To analyze the application of the principle of transparency in the management of School Operational Assistance (BOS) funds at SD Negeri 310 Assorajang, (2) To analyze the application of the principle of accountability in the management of School Operational Assistance (BOS) funds at SD Negeri 310 Assorajang. The variables of this study are Transparency and Accountability of BOS Fund Management. The subjects of this study were the Principal, Treasurer, and Teachers who focused on transparency and accountability in the management of BOS funds. The data collection techniques used were interviews and documentation. The data analysis used was Qualitative Descriptive Analysis. The results of this research show that SD Negeri 310 Assorajang has implemented the principle of transparency in managing BOS funds well, namely involving education unit residents in preparing the RKAS and conveying the realization and recapitulation of the realization of the use of BOS funds which is published through the installation of school information boards. SD Negeri 310 Assorajang has also implemented the principle of accountability in managing BOS funds well. The school has provided education unit data in the Dapodik application, made education unit activity plans and budgets related to the BOS funds received, used BOS funds in accordance with the specified usage components, and made reports on the use of BOS funds in accordance with applicable technical guidelines.